Pengaruh Waktu Perendaman Ikan Teri Dalam Air Panas Terhadap Kadar Formalin - Supriyatin Supriyatin; Hery Prambudi; Ikhwani Ikhwani; Anggun Rizki Lestari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Anchovies are widely consumed by the public and are served in various ways and flavors and variations to make them more attractive and desirable. However, the existence of anchovies today contains a lot of formalin preservatives to last long and not cause big losses. There are many ways to reduce formaldehyde levels in food, one way is to soak it in hot water, because one of the properties of formaldehyde is water soluble. This study aims to determine the formalin content of anchovies before and after soaking in hot water at various time variations and to determine the effect of anchovy soaking time in hot water on formalin content. The research method used in this study is pre-experiment with one-group pretest-postest design while the examination method uses uv-vis spectrophotometer. For data analysis using SPSS program one way anova test. The identification of formalin was done qualitatively using distillation with the addition of chromatopic acid and quantitatively using a spectophotometer with a wavelength of 570 nm. It was found that formalin levels before hot water immersion with a duration of 0 minutes in anchovy rice averaged 26.254 ppm. Samples of anchovy rice after immersion with hot water with the initial temperature of immersion 100°c with a duration of time of 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes obtained the results of the highest decrease in formaldehyde levels at 30 minutes of immersion time averaged 64.25% or 9.385 ppm.